Unveiling the Riddoch phenomenon: a regression analysis of stroke-induced homonymous hemianopia - Tritanon, Oranan; Kimavaha, Suphakarn; Siriyotha, Sukanya; Plant, Gordon T.; Jindahra, Panitha (Frontiers in Neurology, 2025)
IntroductionA subset of patients with homonymous hemianopia can consciously perceive motion within their blind visual fields—a phenomenon known as the Riddoch phenomenon. However, the factors predicting this residual motion perception remain poorly understood. This study aims to identify clinical and neuroanatomical predictors of the Riddoch phenomenon in stroke patients.MethodsWe retrospectively analyzed 32 adult patients (mean age 60.41 years, 34.4% female) with stroke-induced homonymous hemianopia treated at a single center between 2020 and 2023. Clinical data, brain MRI, and visual field assessments were reviewed. The Riddoch phenomenon was quantified as the difference between kinetic motion perception measured by Rama Motion Perimetry (RMP) and static visual perception assessed by Humphrey Visual Field Index (VFI), termed RMP-VFI. Lesions in key visual processing regions—primary visual cortex (V1), motion-sensitive area V5, lateral geniculate nucleus (LGN), and splenium of the corpus callosum—were identified on MRI. Univariate and multiple linear regression models were applied to evaluate predictors of RMP-VFI.ResultsMean RMP-VFI scores were significantly higher in patients with spared V5 compared to those with lesioned V5 (24.1 vs. 1.8, p = 0.033), while no significant differences were observed for other regions. Multiple linear regression revealed diabetes mellitus as a significant negative predictor of RMP-VFI (β = −24.6, 95% CI: −44.47, −4.75; p = 0.017), with spared V5 showing a positive but marginally non-significant association (β = 17.5, 95% CI: −1.61, 36.66; p = 0.071). The model explained 30% of the variance in RMP-VFI (adjusted R2 = 0.25).DiscussionIntegrity of area V5 plays a key role in the Riddoch phenomenon by preserving motion perception despite cortical damage. For the first time, diabetes mellitus is identified as a significant clinical factor negatively influencing residual motion perception, possibly by impairing neural plasticity. These findings enhance understanding of the neural and systemic factors modulating visual recovery after stroke.